The construction pile foundation at mosque in Klang / Muhammad Azwar Mohd. Ashaari - Mohd Ashaari, Muhammad Azwar (Universiti Teknologi MARA, Perak, 2022)
Foundation is the important element of a structure which connects it to the ground, and transfers loads from the structure to the ground. Therefore, this report will discuss about the method for the construction of foundation for the building of school based on practical training. This case study is about building a pile foundation for mosque. The objective of this report is to investigate the construction process of pile that can be broadly characterized by the installation and testing. It will focus on their methods of construction that provides an economical for the environments. To show the importance of a deep foundation as a key component in achieving building design goals, and then to assess the building's workability in terms of meeting JKR's building specifications. This report will also look at the safety of driven pile installation from the Dynamic Pile Testing to prevents pile damage that will gives a better impact for the contractor in the future.